2018
DOI: 10.1080/0361073x.2018.1449591
|View full text |Cite
|
Sign up to set email alerts
|

Severity of sarcopenia is associated with postural balance and risk of falls in community-dwelling older women

Abstract: Sarcopenia negatively affects balance, and both risk and fear of falling in community-dwelling older women. Moreover, this study provides evidence that sarcopenia severity is further associated to reduced balance and imposes an even greater risk of falls in the elderly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
45
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 69 publications
(56 citation statements)
references
References 30 publications
2
45
0
2
Order By: Relevance
“…Review of the titles and abstracts yielded 241 relevant studies for full‐text screening. Thirty‐six studies met all inclusion criteria and were included in this review . A total of 33 studies were included in the meta‐analysis; four of them presented data for both falls and fractures, leaving 20 studies included in the meta‐analysis for falls and 17 studies for fractures …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Review of the titles and abstracts yielded 241 relevant studies for full‐text screening. Thirty‐six studies met all inclusion criteria and were included in this review . A total of 33 studies were included in the meta‐analysis; four of them presented data for both falls and fractures, leaving 20 studies included in the meta‐analysis for falls and 17 studies for fractures …”
Section: Resultsmentioning
confidence: 99%
“…Four studies included a combined group of hospitalized patients with fractures and community‐dwelling individuals without fractures . Two studies reported retrospective data, 20 studies were cross‐sectional, 13 studies were prospective, and 1 study was a randomized controlled trial examining the effect of nutritional supplementation on bone mineral density and risk of falls . Most of the studies were performed in Europe (12 studies), and Asia (12 studies), followed by Australia (5 studies), South America (4 studies), and North America (3 studies) .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations